2020
DOI: 10.1177/0883073820962927
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Emotional Distress Among Mothers of Sons With Muscular Dystrophy as Compared to Sex- and Age Group–Matched Controls

Abstract: The health-related quality of life and emotional distress among mothers of sons with Duchenne or Becker muscular dystrophies (n = 82) were compared to sex- and age group–matched controls (n = 26). Participants self-reported health-related quality of life for themselves and their son(s), emotional distress, and mood/anxiety-related medication. Mothers reported poorer health-related quality of life across all domains of their health-related quality of life, as well as higher levels of emotional distress. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Decreased health-related quality of life and emotional distress among mothers of sons with muscular dystrophy have been described in a study conducted at Nationwide Children's Hospital (Jackson et al, 2021). When compared to sex and age group matched controls, mothers of sons with muscular dystrophy reported poorer healthrelated quality of life across all domains of their health-related quality of life, as well as higher levels of emotional distress (Jackson et al, 2021).…”
Section: Clinical Evaluation Of Female Carriersmentioning
confidence: 99%
“…Decreased health-related quality of life and emotional distress among mothers of sons with muscular dystrophy have been described in a study conducted at Nationwide Children's Hospital (Jackson et al, 2021). When compared to sex and age group matched controls, mothers of sons with muscular dystrophy reported poorer healthrelated quality of life across all domains of their health-related quality of life, as well as higher levels of emotional distress (Jackson et al, 2021).…”
Section: Clinical Evaluation Of Female Carriersmentioning
confidence: 99%
“…In a review, Landfeldt et al found [ 22 ] the informal care of patients with DMD was associated with a substantial burden, and they recommended further research to better understand the relationship between clinical implications and progression of disease and caregiver burden. A cross-sectional study by Jackson et al [ 23 ] examined mothers’ demographic characteristics and their sons’ QoL-related factors to identify which ones contribute to poorer health-related QoL and greater emotional distress. Mothers’ perception of their sons’ health-related QoL is a significant predictor of their own health-related QoL and emotional distress.…”
Section: Introductionmentioning
confidence: 99%